Efficiency of the Summer Monsoon in Generating Streamflow Within a Snow‐Dominated Headwater Basin of the Colorado River. Issue 23 (5th December 2020) - Carroll, Rosemary W. H.; Gochis, David; Williams, Kenneth H.
Abstract: The North American Monsoon occurs July–September in the central Rocky Mountains bringing significant rainfall to Colorado River headwater basins. This rain may buffer streamflow deficiencies caused by reductions in snow accumulation. Using a data‐modeling framework, we explore the importance of monsoon rain in streamflow generation over historical conditions in an alpine basin. Annually, monsoon rain contributes 18 ± 7% water inputs and generates 10 ± 6% streamflow. The bulk of rain supports evapotranspiration in lower subalpine forests. However, rains have the potential to produce appreciable streamflow at higher elevations where soil moisture storage, forest cover, and aridity are low and rebound late season streamflow 64 ± 13% from simulated reductions in spring snowpack as a function of monsoon strength. Interannual variability in monsoon efficiency to generate streamflow declines with low snowpack and high aridity, implying the ability of monsoons to replenish streamflow in a warmer future with less snow accumulation will diminish. Plain Language Summary: Monsoon rains bring much needed summer moisture to the southwestern United States, but it remains unclear whether rains have a significant effect on streamflow in the snow‐dominated headwaters of the Colorado River. Lack of understanding is largely due to the difficulty in measuring rain and snowfall in steep, mountainous basins, and the effect both have on seasonal plant consumption of water. Using a hydrological model populated with ground, airborne, and synthesized climate data, we compare relative efficiency of monsoon rain to generate stream water over multiple decades in an alpine basin. Monsoon rains deliver one fifth of the basin's water and produce 10% the annual streamflow, with additions largely confined to the upper elevations of the watershed where soils are thin, water is plentiful, and forests are less abundant. In contrast, lower elevations contain dense aspen and conifer forests that consume monsoon rain and limit streamflow response. Subsequently, even strong monsoon events cannot fully replenish lost snow. Summer rains produce more streamflow during cooler years with large snow accumulation. This hints that streamflow from summer rain may diminish in a warmer future with less snow. Key Points: Monsoon rains generate 10 ± 6% of annual streamflow while late spring snowfall delivers twice as much for the same water input The influence of monsoon rain on streamflow is half of late spring snow due to evapotranspiration in the lower subalpine forest Monsoon efficiency in generating streamflow decreases in warm years with low snow accumulation